Depicting Indonesian values in Arifin C. Noer’s The Bottomless Well for ILFS learning - Maria Vicentia Eka Mulatsih; Bonifasius Widharyanto (LITERA, 2022)
Learning language is not merely about its structure or words, it deals with certain values as a representative of the culture. Arifin C Noer’s play entitled The Bottomless Well portrays some Indonesian values that can be taught for learning Indonesian language for foreign speakers (ILFS). Focusing on some Indonesian values portrayed in the play and some ILFS learning practices, this article closely analyzes its content using document analysis method and describes the teaching practices qualitatively. Some Indonesian values found in the play are mutual help, social solidarity, persistency, work ethic, frugality, spirituality and independency. These Indonesian values portrayed in the play are useful as  a material for reading, writing, speaking, listening lessons. Specifically, in a drama class, various ILFS learning activities using this play are 1) reading aloud, 2) having monologue, 3) dramatic reading in groups, 4) conducting mini role play, and 5) completing the reflection process. Keywords: Indonesian values, ILFS learning, The Bottomless WellPenggambaran nilai-nilai Indonesia dalam karya Arifin C. Noer Sumur Tanpa Dasar untuk pembelajaran BIPA AbstrakPembelajaran Bahasa tidak hanya mengenai struktur ataupun kata, hal ini berhubungan dengan nilai-nilai tertentu sebagai representasi dari budaya. Drama Arifin C. Noer berjudul Sumur Tanpa Dasar menggambarkan beberapa nilai bangsa Indonesia yang dapat diajarkan dalam pembelajaran Bahasa Indonesia bagi penutur asing (BIPA). Berfokus pada beberapa nilai budaya Indonesia dan praktek pengajaran BIPA, artikel ini menganalisis isi drama secara lebih dekat menggunakan analisis dokumen dan mendeskripsikan praktek-praktek pengajaran secara kualitatif. Beberapa nilai budaya Indonesia yang ditemukan dalam drama tersebut adalah gotong royong, solidaritas sosial, ketekunan, daya juang, hemat, spiritualitas dan kemandirian. Nilai Indonesia ini yang tergambar dalam drama berguna sebagai materi pembelajaran membaca, menulis,  berbicara dan mendengarkan. Secara spesifik di kelas drama, beragam aktifitas pembelajaran BIPA menggunakan drama ini adalah 1) pembacaan lantang, 2) monolog, 3) pembacaan drama dalam grup, 4) mini drama, dan 5) refleksi.Kata kunci: nilai-nilai Indonesia, praktek pengajaran BIPA, “Sumur Tanpa Dasar”